IMAGE PROCESSING APPARATUS, 3D MODEL GENERATION METHOD, AND PROGRAM (2020)
The present technology relates to an image processing apparatus, a 3D model generation method, and a program capable of reducing failed image capturing in multi-view image capturing for 3D model generation. The image processing apparatus includes a 3D region calculation unit that generates a 3D region of image capturing ranges generated from a plurality of multi-view images, and a determination unit that determines a situation in which an image capturing device captures a subject on the basis of a region image obtained by projecting the 3D region onto a specific viewpoint and a subject image from the image capturing device corresponding to the specific viewpoint. The present technology can be applied to, for example, an image processing apparatus for 3D model generation.